2020
DOI: 10.1001/jamaoncol.2019.4120
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of Plasma Microbial Cell-Free DNA Sequencing to Predict Bloodstream Infection in Pediatric Patients With Relapsed or Refractory Cancer

Abstract: IMPORTANCE Bloodstream infection (BSI) is a common, life-threatening complication of treatment for cancer. Predicting BSI before onset of clinical symptoms would enable preemptive therapy, but there is no reliable screening test. OBJECTIVE To estimate sensitivity and specificity of plasma microbial cell-free DNA sequencing (mcfDNA-seq) for predicting BSI in patients at high risk of life-threatening infection. DESIGN, SETTING, AND PARTICIPANTSA prospective pilot cohort study of mcfDNA-seq for predicting BSI in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(99 citation statements)
references
References 15 publications
1
75
0
Order By: Relevance
“…There are already significant efforts to move next-generation sequencing (NGS) to the heart of the microbiology laboratory as a universal tool for pathogen detection and identification (102), antimicrobial resistance prediction, and molecular epidemiology (103,104), where it has been scientifically demonstrated to be promising (105)(106)(107). However, further studies are needed to better identify the benefits of the integration of NGS into current testing algorithms (108)(109)(110).…”
Section: Consolidation and Implementation Of New(er) Technologiesmentioning
confidence: 99%
“…There are already significant efforts to move next-generation sequencing (NGS) to the heart of the microbiology laboratory as a universal tool for pathogen detection and identification (102), antimicrobial resistance prediction, and molecular epidemiology (103,104), where it has been scientifically demonstrated to be promising (105)(106)(107). However, further studies are needed to better identify the benefits of the integration of NGS into current testing algorithms (108)(109)(110).…”
Section: Consolidation and Implementation Of New(er) Technologiesmentioning
confidence: 99%
“…Earlier studies have shown that mNGS can reliably detect pathogens from patients with febrile illness (Wylie et al, 2012), respiratory and gastric/ digestive infections (Joensen et al, 2017;Mizrahi et al, 2017), and acute encephalitis/encephalopathy (Kawada et al, 2016). In addition, mNGS can help identify causative microorganisms for patients with suspected BSIs with high sensitivity and specificity (Gyarmati et al, 2016;Brenner et al, 2018;Goggin et al, 2019). ddPCR, as an emerging versatile tool with high sensitivity and excellent accuracy and precision, has been increasingly used in multiple clinical scenarios including BSIs (Li et al, 2018;Abram et al, 2020;Wouters et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…There are case reports of mNGS detecting rare pathogens (11)(12)(13) when conventional tests were negative. However, for the vast majority of cases, organisms identified by mNGS were common pathogens that were also detected by conventional testing methods (7,9).…”
mentioning
confidence: 98%
“…Case series have shown that mNGS can identify the etiology of infection in patients with complicated community-acquired pneumonia or in immunocompromised patients with invasive fungal disease when traditional or other advanced diagnostic methods are negative (5,6). In a prospective cohort study of pediatric patients with relapsed or refractory cancer, mNGS predicted bloodstream infection 3 days prior to blood culture in 12 of 16 cases (7). mNGS tests bear the promise of being noninvasive, with the ability to detect both uncommon and common pathogens in many different clinical scenarios.…”
mentioning
confidence: 99%